(untitled) (Research, Society and Development, 2023)
The purpose of this case report is to describe the complexity of dental management of a pediatric patient with lamellar ichthyosis. A 9-year-old male patient was referred by the pediatrician to the special needs’ clinic with a major complaint of "tooth in the roof of the mouth", according to the person in charge. The patient’s mother reported that he was diagnosed with lamellar ichthyosis at birth and regularly followed up with a medical team, including a cardiologist, due to the presence of mild pulmonary valve stenosis. The physical examination revealed presence of skin peeling, everted lip, mouth breathing, cognitive deficit, and speech delay. The intraoral clinical examination showed mixed dentition, absence of caries lesions and presence of supernumerary teeth on the palate, between teeth 11 and 21, which was confirmed by radiographic examination. Although he was cleared by the pediatrician and cardiologist for the procedure under general anesthesia, this procedure in the hospital setting was interrupted at the last minute and contraindicated by the anesthesiologist, as it would be a high risky due to the patient’s airway conditions. Thus, one month later, the patient’s surgery was performed under local anesthesia on an outpatient basis under sedation and protective stabilization. The patient remains on follow-up and receiving preventive treatment. Thus, it is fundamental that there is a multidisciplinary approach of these patients to prevent possible complications resulting from dental procedures. In addition, regular dental monitoring is essential to avoid subjecting the patient to invasive procedures.